ChemInform Abstract: Unveiling the Reactivity of Propargylic Hydroperoxides under Gold Catalysis. Issue 30 (4th July 2013) - Alcaide, Benito; Almendros, Pedro; Quiros, M. Teresa; Lopez, Ramon; Menendez, Maria I.; Sochacka‐Cwikla, Aleksandra
Abstract This gold‐catalyzed reaction of primary and secondary propargylic hydroperoxides with a variety of O‐ and C‐nucleophiles furnishes β‐functionalized ketones.